2021
DOI: 10.1108/bfj-02-2021-0148
|View full text |Cite
|
Sign up to set email alerts
|

Community enterprise consumers’ intention to purchase organic rice in Thailand: the moderating role of product traceability knowledge

Abstract: PurposeOrganic rice forms the largest portion of the Thai organic food market. Because of its increasing popularity, marketers need to better understand consumer behaviour to address emerging concerns regarding product safety and quality and to tailor better marketing strategies relevant to the development of organic rice. As such, this study aims to examine consumers' purchase intention towards organic rice, using traceability information, and to investigate the direct and moderating roles of product traceabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
38
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 94 publications
10
38
1
Order By: Relevance
“…The study's analysis of the function and influence of consumer awareness of organic food on food safety is another important contribution. This empirical finding also addresses the ongoing discussion regarding whether consumer knowledge of traceability and awareness of organic food could lead to such relationships (Hong et al, 2020;Cavite et al, 2021). The empirical research in this paper supports this position by demonstrating that the relationship between food safety trust and consumer wellbeing can be moderated by consumers' awareness of organic food.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The study's analysis of the function and influence of consumer awareness of organic food on food safety is another important contribution. This empirical finding also addresses the ongoing discussion regarding whether consumer knowledge of traceability and awareness of organic food could lead to such relationships (Hong et al, 2020;Cavite et al, 2021). The empirical research in this paper supports this position by demonstrating that the relationship between food safety trust and consumer wellbeing can be moderated by consumers' awareness of organic food.…”
Section: Discussionsupporting
confidence: 65%
“…To better understand consumer expectations regarding organic food supply chain traceability practices, it is therefore essential to understand the safety trust of organic food traceability. Therefore such understanding helps producers and marketers of traceable organic foods develop more informed marketing strategies ( Cavite et al, 2021 ). Going beyond economic impacts to address customer happiness and social value of traceability, this research seeks to investigate how supply chain firms employ traceability technologies to increase consumer consumption values, often results consumer wellbeing.…”
Section: Introductionmentioning
confidence: 99%
“…As found in other studies (Al-Swidi et al , 2014; Moons and de Pelsmacker, 2015; Zhang et al , 2018; Gungaphul et al , 2022), PBC also showed no significant relation to PI. Cavite et al (2022) also reported a similar finding in their studies of intention using the TPB model. In the proposed model, accessibility, availability and convenience were the factors used to indicate the PBC construct.…”
Section: Methodssupporting
confidence: 73%
“…Among the main objectives of a CE are production, marketing and selling of locally produced goods at a more affordable price than big companies producing the same product (Somswasdi et al , 2015). Several types of CEs are present in Thailand, such as mushroom (Changwatchai and Santipolvut, 2015), textile (Distanont et al , 2017; Naipinit et al , 2016; Seenuankaew et al , 2018), curry paste (Seenuankaew et al , 2018), handicrafts, fishery, forestry and wood products (Naipinit et al , 2016) and rice (Cavite et al , 2021c; Prasertwattanakul and Ongkunaruk, 2015; Raungpaka and Savetpanuvong, 2017; Ruangsarakul et al , 2019; Seenuankaew et al , 2018). The most common of them is the RPCE.…”
Section: Review Of Literaturementioning
confidence: 99%
“…This approach has been widely applied in most organic food products (Jitrawang and Krairit, 2019;Pandey et al, 2019). Several studies have Community enterprise development also started to explore the role of product traceability (Cavite et al, 2021c;Chen et al, 2020;Spence et al, 2018;Wang and Tsai, 2019). This can be applied to CE's organic rice products considering consumers' concern for safer and healthier foods.…”
Section: Product Design and Marketingmentioning
confidence: 99%